PERSEPSI ORANG TUA TERHADAP PERAN KOMUNIKASI DALAMPENGGUNAAN GADGET PADA ANAK USIA DINI - Nizma Ammara Zahira (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2025)
This study explores parents’ perspectives on the role of communication in young children’s gadget usage. With the increasing prevalence of technology and gadgets among children, it is crucial to understand how parents implement communication strategies to guide gadget usage and mitigate its negative impacts. This research adopts a qualitative approach using simple interview methods involving parents of young children. Data were analyzed descriptively to understand parents’ experiences and views on the communication strategies they apply. The findings reveal that parents employ various methods, such as setting time limits and providing simple explanations to their children, although they often face challenges in implementation. This study highlights the importance of consistent and open communication between parents and children in fostering more mindful gadget usage habits